2018
DOI: 10.1371/journal.pone.0202794
|View full text |Cite
|
Sign up to set email alerts
|

Human milk enriched with human milk lyophilisate for feeding very low birth weight preterm infants: A preclinical experimental study focusing on fatty acid profile

Abstract: BackgroundHuman milk, with essential nutrients and long chain polyunsaturated fatty acids (LC-PUFAs) such as the omega 3 and 6 fatty acids is important for development of the central nervous system and the retina in very low birth weight infants (<1,500 g). However, breast milk may not be sufficient to meet these needs. The possibility of supplementing breast milk with a lyophilisate of human milk was explored in this study. The objectives of this study were to determine the total lipid content and the lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 77 publications
(82 reference statements)
0
9
0
2
Order By: Relevance
“…Apart from the findings by Salcedo et al (2015) on the successful reduction of germs in breast-milk after freeze-drying, it was shown that storage of freeze-dried milk did not show a significant influence upon several biological properties of human milk such as total antioxidant capacity and fatty acid profile of milk [ 21 , 22 , 23 , 24 ]. The storage and transport of milk powder is also considerably less complicated in the hospital setting and makes possible longer storage than in the case of pasteurized milk, which must be frozen [ 21 , 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the findings by Salcedo et al (2015) on the successful reduction of germs in breast-milk after freeze-drying, it was shown that storage of freeze-dried milk did not show a significant influence upon several biological properties of human milk such as total antioxidant capacity and fatty acid profile of milk [ 21 , 22 , 23 , 24 ]. The storage and transport of milk powder is also considerably less complicated in the hospital setting and makes possible longer storage than in the case of pasteurized milk, which must be frozen [ 21 , 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the powder can be easy to reconstitute at a given volume to obtain the required caloric and nutrition value of milk for preterm infants [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Honduras has extensive coastlines in the Atlantic and Pacific oceans, but fish consumption (which is not from sea origin) is very low, as shown in the results of the study. The AA content in BM is usually stable [3], fluctuating slightly around 0.5% of total fatty acids as it is mostly derived from maternal reserves [29]; however, the DHA concentration is much more variable, constituting 0.1% to 1.0% of total fatty acids [5]. To maintain an adequate concentration of AA and DHA, it is recommended that at least 200 mg/day of preformed DHA be consumed daily [2,57], however, consumption in our sample was found to be well below the recommendation (40 mg/day).…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding (BF) from healthy, well-nourished mothers is the ideal food to meet the nutritional demands of full-term babies [1][2][3][4] promoting their growth and the development of their gastrointestinal [5,6], immunological [7] and neurological [8] systems, owing to its unique content of essential nutrients [9,10], hormones, antibodies and biologically-active molecules [11,12]. The World Health Organization (WHO) recommends exclusive BF (EBF) for the first six months of life and continuing it in conjunction with feeding for two years or more [13,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation